2019
DOI: 10.1111/pbi.13128
|View full text |Cite
|
Sign up to set email alerts
|

Efficient genetic transformation and CRISPR/Cas9‐mediated genome editing in Lemna aequinoctialis

Abstract: Summary The fast growth, ease of metabolic labelling and potential for feedstock and biofuels production make duckweeds not only an attractive model system for understanding plant biology, but also a potential future crop. However, current duckweed research is constrained by the lack of efficient genetic manipulation tools. Here, we report a case study on genome editing in a duckweed species, Lemna aequinoctialis, using a fast and efficient transformation and CRISPR/Cas9 tool. By optimizing currently available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 79 publications
(113 reference statements)
0
28
1
Order By: Relevance
“…The duckweed used in this study was previously identified and named L. aequinoctialis 6002 (Liu, Wang, et al, 2019). L. aequinoctialis 6002 was cultured in Schenk & Hildebrandt (SH) liquid medium supplemented with 10 g/L sucrose, and maintained in a growth chamber at 24°C under a light intensity of 110 μmol m −2 s −1 and a photoperiod of 16 hr (light):8 hr (dark).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The duckweed used in this study was previously identified and named L. aequinoctialis 6002 (Liu, Wang, et al, 2019). L. aequinoctialis 6002 was cultured in Schenk & Hildebrandt (SH) liquid medium supplemented with 10 g/L sucrose, and maintained in a growth chamber at 24°C under a light intensity of 110 μmol m −2 s −1 and a photoperiod of 16 hr (light):8 hr (dark).…”
Section: Methodsmentioning
confidence: 99%
“…As a supplement to the screening of natural germplasms, the transgenic technology and DNA mutagenesis technology are efficient and frequently used methods to obtain better genetic traits. Genetic manipulation has already been performed in some species in the duckweed family (Chhabra, Chaudhary, Sainger, & Jaiwal, 2011; Vunsh et al., 2007; Yang et al., 2018) including gene overexpressing, artificial microRNA‐induced posttranscriptional gene silencing, and CRISPR/Cas9‐mediated genome editing (Cantó‐Pastor et al., 2015; Liu, Wang, et al, 2019; Yang et al., 2017). It can be anticipated that these approaches will definitely help us to uncover the mechanisms underlying starch accumulation in duckweed.…”
Section: Introductionmentioning
confidence: 99%
“…They found that conjunction of N6-(2-Isopentenyl) adenine (2IP) (1 mg/L) and 2,4-dichlorophenoxyacetic (2,4-D) (10 mg/L) effectively induced callus formation, and the addition of indole acetic acid (4 mg/L) and kinetin (1 mg/L) successfully induced frond regeneration. Subsequently, the tissue culture of a wide range of Lemna was established, including Lemna aequinotialis [ 53 ], Lemna minor [ 54 , 55 ], and Lemna turionifera [ 56 ]. Li et al [ 57 ] established an efficient tissue culture cycle for Spirodela oligorrhiza , Landoltia punctata , and Lemna gibba .…”
Section: Genetic Transformation System For Duckweedmentioning
confidence: 99%
“…The transformation efficiency varies, depending on the frond, callus, and hormone. The transform efficiency of Lemna reaches 10%–94% (Chhabra, Chaudhary, Sainger, & Jaiwal, 2011; Liu, Wang, et al, 2019; Yang, Fang, et al, 2018), while it is 5%–13% in Spirodela (Rival et al., 2008; Vunsh et al., 2007; Yang, Li, et al, 2018). By contrast, Wolffia has the lowest transform efficiency of about 0.14%–0.4% (Heenatigala et al., 2018; Pavel et al., 2018).…”
Section: Duckweed In the Production Of High Value‐added Productsmentioning
confidence: 99%